Estimation of feedwater heater parameters based on a grey-box approach - Barszcz, Tomasz; Czop, Piotr (Zielona Góra: Uniwersytet Zielonogórski)
The first-principle modeling of a feedwater heater operating in a coal-fired power unit is presented, along with a theoretical discussion concerning its structural simplifications, parameter estimation, and dynamical validation. The model is a part of the component library of modeling environments, called the Virtual Power Plant (VPP). The main purpose of the VPP is simulation of power generation installations intended for early warning diagnostic applications
Keywords: first-principle model; system identification; heater; heat exchanger; grey-box